Attention to diversity in higher education: Economic and cultural factors for labor market insertion - Apaza-Panca, Cynthia Milagros; Maquera-Luque, Pedro Jesús; Saico, Cristóbal Rufino Yapuchura; Noriega, Carlomagno Sancho; Quisocala, Alfredo Ivan Olaguivel (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study was to determine how socioeconomic and cultural factors influence the labor market insertion of graduates from three study programs at the National University of Northern Border, Peru. The research design was non-experimental and cross-sectional. The population consisted of 825 graduates and a sample of 263 graduates. The data collection technique was a survey, and the instrument was a questionnaire. The study used discrete choice Logit and Probit models; the following variables were identified as socioeconomic and cultural factors that positively influence labor market insertion: age, sex, professional background, marital status, educational level, area of residence, work activity, association affiliation, monthly income, seniority, length of service, home ownership, basic services (internet, cable), language proficiency, media, place of birth, mother’s education, and use of social media (WhatsApp). On the other hand, the variables related to the number of children, leisure activities, housing materials, television preferences, and father’s education decrease the likelihood of a graduate working. In conclusion, these social, economic, and cultural factors explain the labor market integration of university graduates from a diversity perspective. The findings can guide the design of educational public policies, considering attention to diversity. This research expands the literature on attention to diversity and labor market integration, especially factors that determine whether graduates can enter the labor market from a diversity perspective.